Assessment of prescription writing skills among undergraduate medical students - Sudha, M. J.; Viveka, S.; Remya, S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The existing medical undergraduate curriculum includes training in prescription writing in second phase under pharmacology and Therapeutics. This study evaluates the prescription writing skills of undergraduate medical students and interns and need for emphasis on prescription writing during various phases of learning process in medical undergraduates. Methods: After obtaining institutional ethics committee approval, we recruited 4th to 8th semester medical undergraduate students and interns into the study, who gave written informed consent. They were given a pilot-tested, pre-evaluated questionnaire addressing the issues of prescription writing. They were asked to prescribe for a common clinical scenario. Their prescriptions were analysed for various parameters as indicated in WHO guidelines. Results: Of the 350 medical undergraduate students and interns invited, 281 of them participated in the study. 169 participants (60.1%) agree that they have not written a formal prescription to any patient when the questionnaire was administered. 134 participants (47.6 %) feel that undergraduate training has not prepared them for prescribing properly. 90% of participants said reinforcing classes during 3rd, 4th year and during Compulsory Routine Rotatory Internship will be beneficial. Though 220 participants have opined that generic name should be used while prescribing, only 124 have actually used generic names in their prescriptions. Fifteen participants have failed to write the symbol while prescribing. All 121 interns in the study have used brand names while prescribing. Conclusions: There are widespread lacunae in prescription writing by medical undergraduates. There is perceived need for reinforcement sessions at third and final phase of undergraduate education to address this gap. Most participants opine that clinicians do not discuss this issue during case discussion. There is knowledge and practice gap in using generic names while prescribing.